Electrochemical properties of thermally treated platinized Ebonex ®with low content of Pt - Kasian, O. I.; Luk'Yanenko, T. V.; Demchenko, Pavlo Yu.; Gladyshevskii, R. E.; Amadelli, Rossano; Velichenko, A. B. (Electrochimica Acta, 2013)
Effect of thermal treatment on the physicochemical and electrochemical properties of platinized Ebonex®electrodes, containing low amount of Pt has been investigated. New phases in systems Ti-O (310°C) andPt-Ti-O (410°C) were found for treated Ebonex®that affects electrochemical behavior of electrodes.Ebonex®/Pt-electrodes were shown to be n-type highly doped semiconductors, as well as Ebonex ®.Increase in treatment temperature leads to both oxidation of titanium suboxides and diffusion of Ptdeep into substrate and results in shift of flatband potential to positive values and decrease in donor con-centration as a rule. The peak of reduction of Pt phase oxides on the cathodic branch of voltammogramscould be correlated with electrocatalytic activity of platinized Ebonex®-electrodes since it characterizesthe amount of electrochemically active platinum on the electrode surface. Thermally treated platinizedEbonex®anodes could be applied in a trivalent chromium electroplating bath. © 2013 Elsevier Ltd. All rights reserved.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Electrocatalytic activityn-Type semiconductor; Pt